Experiences and Needs of Patients with Esophageal Cancer Receiving Esophagectomy: A Qualitative Longitudinal Study - Sun AY; Xu XX; Zheng Y; Wang YY; Ma RC (Patient Preference and Adherence)
Ai-Ying Sun,1 Xiao-Xia Xu,2 Yan Zheng,1 Ying-Ying Wang,1 Rui-Chen Ma1 1Department of Thoracic Surgery, The Affiliated Cancer Hospital of Zhengzhou University & Henan Cancer Hospital, Zhengzhou, Henan, People’s Republic of China; 2Department of Nursing, The Affiliated Cancer Hospital of Zhengzhou University & Henan Cancer Hospital, Zhengzhou, Henan, People’s Republic of ChinaCorrespondence: Rui-Chen Ma, The Affiliated Cancer Hospital of Zhengzhou University & Henan Cancer Hospital, No. 127 Dongming Road, Zhengzhou, Henan, 450008, People’s Republic of China, Tel +86 13633792691, Email 1003373360@qq.comPurpose: With the incidence of esophageal cancer increasing year by year, it is very important to understand the disease experience of patients at different stages of the cancer journey. Supportive care is a long-term task for patients with esophageal cancer. This study was designed to explore the disease experiences and needs of esophageal cancer patients receiving esophagectomy at key time points in their cancer journey.Patients and Methods: A qualitative longitudinal study based on the Timing It Right framework. A purposive sampling method was used, and a sample of 17 patients completed 79 interviews. One-to-one and semistructured interviews were conducted in a tertiary cancer hospital in China from March to August 2024, and Colaizzi’s method was used to analyze data.Results: Twelve subthemes were identified: the diagnosis phase (deep in fear and excessive worry, desire for comprehensive and professional information), the perioperative phase (multiple pressures and looking forward to humanistic care, not adapted to the ward environment and sleep disorders, urgently require for symptom management program), the discharge preparation phase (home-based rehabilitative information and medication guidance, home self-monitoring and continuous care needs), the adjustment phase (loss of normal “daily life”, avoidant social behavior, social support needs), and the adaptation phase (improved health management behavior, integration into society needs and eager for national policy support).Conclusion: The needs of esophageal cancer patients vary during the diagnosis and treatment process. Continuous and dynamic care should be provided for patients according to their needs in different stages of the disease.Keywords: disease experience, esophageal cancer, needs, qualitative research, surgery